Analisis Kebijakan Publik tentang Cuti ASN berdasarkan SE Gubernur Jambi No. 178/SE/BKD-5.2/1/2025 - Nurphi, Febrainy (Lembaga Yasin AlSys, 2025)
The regulation of leave entitlements for State Civil Apparatus (ASN) is a crucial aspect of the public personnel system, aiming to balance individual rights with the smooth operation of government administrative services. This study analyzes public policy concerning ASN leave based on the Circular Letter (SE) of the Governor of Jambi Number 178/SE/BKD-5.2/1/2025. The primary focus lies on the legal review and implementation of the policy within the framework of prevailing legislation, particularly Law Number 5 of 2014 on ASN, Government Regulation Number 94 of 2021 on Civil Servant Discipline, and BKN Regulation Number 24 of 2017 as amended by BKN Regulation Number 7 of 2021. A normative juridical approach was used, analyzing primary and secondary legal materials to evaluate the legal force and administrative implications of the circular. Although a circular letter does not carry binding legal authority equivalent to statutory regulations, it functions as an internal directive that must be adhered to by ASN within the bureaucratic discipline framework. The analysis reveals that the Governor’s Circular strengthens the orderly exercise of ASN leave rights, restricts the use of official facilities during leave, and provides an administrative basis for enforcing discipline and imposing sanctions for violations. Based on the principles of propriety, legal certainty, and good faith, the circular serves as both a preventive and corrective administrative instrument within the civil service legal system. The study concludes that this SE plays a vital role in supporting effective governance, reinforcing ASN discipline, and ensuring public accountability—particularly in managing annual leave and extended holidays within public service sectors.